2013
DOI: 10.1016/j.ecresq.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home environment and center-based child care quality on children's language, communication, and literacy outcomes

Abstract: a b s t r a c tThis study examined the joint effects of home environment and center-based child care quality on children's language, communication, and early literacy development, while also considering prior developmental level. Participants were 95 children (46 boys), assessed as toddlers (mean age = 26.33 months; Time 1) and preschoolers (mean age = 68.71 months; Time 2) and their families. At both times, children attended center-based child care classrooms in the metropolitan area of Porto, Portugal. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 36 publications
4
42
0
1
Order By: Relevance
“…Within the variety of socio-economic status (SES)—related variables, parental and specifically maternal education has been shown to have strong influence on the language input provided and thus on children’s vocabulary acquisition (e.g., Hoff, 2013 , Magnuson, Sexton, Davis-Kean, & Huston, 2009 , but for contradictory results see also Letts, Edwards, Sinka, Schaefer, & Gibbons, 2013 ; Luijk et al, 2015). Previous research has also demonstrated that the relative influence of family-related factors (e.g., parental education and parenting quality) is larger than the influence of daycare related variables (Belsky, Vandell et al, 2007; Ebert et al, 2013 ; NICHD, 2006; Pinto, Pessanha, & Aguiar, 2013). In the last decades research has concentrated on compensatory efforts, demonstrating substantial developmental gains, specifically for disadvantaged children in high-quality daycare arrangements (e.g., Magnuson, Ruhm, & Waldfogel, 2007 ; for reviews see Burger, 2010 ; Jalongo & Sobolak, 2011) or for high-quality child-caregiver interactions (Vernon-Feagans, Bratsch-Hines, & The Family Life Project Investigators, 2013), while emphasizing the cumulative negative effects of social disadvantages (Ebert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Within the variety of socio-economic status (SES)—related variables, parental and specifically maternal education has been shown to have strong influence on the language input provided and thus on children’s vocabulary acquisition (e.g., Hoff, 2013 , Magnuson, Sexton, Davis-Kean, & Huston, 2009 , but for contradictory results see also Letts, Edwards, Sinka, Schaefer, & Gibbons, 2013 ; Luijk et al, 2015). Previous research has also demonstrated that the relative influence of family-related factors (e.g., parental education and parenting quality) is larger than the influence of daycare related variables (Belsky, Vandell et al, 2007; Ebert et al, 2013 ; NICHD, 2006; Pinto, Pessanha, & Aguiar, 2013). In the last decades research has concentrated on compensatory efforts, demonstrating substantial developmental gains, specifically for disadvantaged children in high-quality daycare arrangements (e.g., Magnuson, Ruhm, & Waldfogel, 2007 ; for reviews see Burger, 2010 ; Jalongo & Sobolak, 2011) or for high-quality child-caregiver interactions (Vernon-Feagans, Bratsch-Hines, & The Family Life Project Investigators, 2013), while emphasizing the cumulative negative effects of social disadvantages (Ebert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have not combined teachers', parents', and external observers' perceptions and assessments of ECE, particularly for toddlers' classrooms. Assuming the influence of contexts of education and care on children's short-term and long-term outcomes, studies on quality of ECE have been developed in the last years in Portugal (e.g., Pinto et al 2013;Abreu-Lima et al 2013). This research context substantiates the need to understand Portuguese parents' and teachers' perceptions of quality, features usually accepted by researchers.…”
Section: Parents' and Teachers' Assessments Of Ece Environmentmentioning
confidence: 99%
“…In Portugal, in the last decades, a public investment has been made in order to increase the coverage rate of childcare services for infants and toddlers, dependent on the Ministry of Solidarity, Employment and Social Security, and the coverage rate of preschools (children between 3 and 6 years old), dependent on the Ministry of Education (Abreu-Lima et al 2013;Pinto et al 2013). However, research projects on ECE services for infants and toddlers, and initiatives to improve their quality, are still necessary (Barros and Aguiar 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In classrooms of 3-to 6-year-olds rated using the Early Childhood Environment Rating Scale (Harms & Clifford, 1980;Harms, Clifford, & Cryer, 1998), two studies (Pinto, Pessanha, & Aguiar, 2013) found that 97% and 93% of the centers had scores in the range of 3 to 4 (minimal quality), no classrooms were below 3 (inadequate quality), and only 5% to 8% had scores above 5 (good quality). Barros and Aguiar (2010) reported that in toddler classrooms rated using the Infant/Toddler Environment Rating Scale (Harms, Cryer, & Clifford, 1990), 61% of classrooms had scores below 3 (inadequate quality), 39% had scores between 3 and 5 (minimal quality), and no classrooms had scores above 5 (high quality).…”
Section: The Present State Of Group Child Care In Portugalmentioning
confidence: 98%
“…Barros and Aguiar (2010) reported that in toddler classrooms rated using the Infant/Toddler Environment Rating Scale (Harms, Cryer, & Clifford, 1990), 61% of classrooms had scores below 3 (inadequate quality), 39% had scores between 3 and 5 (minimal quality), and no classrooms had scores above 5 (high quality). Pinto et al (2013) found a quality score range from 1.76 to 3.47 (M ¼ 2.55, SD ¼ 0.42), meaning that all classrooms were of inadequate to minimal quality. Another nationally representative study with 1,691 preschool groups of 3-to 6-year-olds reported a mean group size of 20.0 children (SD ¼ 4.1) and 99.6% groups with up to 25 children, and there was an average 7.9:1 child:adult ratio (Conselho Nacional de Educação, 2011).…”
Section: The Present State Of Group Child Care In Portugalmentioning
confidence: 99%